Codeine in paediatrics: pharmacology, prescribing and controversies. Issue 3 (16th March 2016) - Andrzejowski, Paul; Carroll, Will
Abstract : Codeine is a drug that until recently was widely used in children. It was endorsed by the WHO as the second step on the analgesic ladder for cancer pain and has been used routinely for postoperative and breakthrough pain. Recently, its safety and efficacy have been called into question, following deaths after adenotonsillectomy was associated with its use. This has led to regulation by the US Food and Drug Administration, European Medicines Agency and the UK Medicines and Healthcare products Regulatory Agency to place significant restrictions on its use, and some centres have stopped using it altogether. In this article, we discuss the developmental pharmacology underpinning its action, reviewing what is known about the pharmacokinetics, pharmacodynamics and pharmacogenetics in children, how this relates to prescribing, as well as the practical issues and the recent regulatory framework surrounding its use.